Onchocerciasis in the Ntui Health District of Cameroon: epidemiological, entomological and parasitological findings in relation to elimination prospects - Joseph Nelson Siewe Fodjo; Leonard Ngarka; Wepnyu Yembe Njamnshi; Peter Ayuk Enyong; Anne-Cécile Zoung-Kanyi Bissek; Alfred Kongnyu Njamnshi (Parasites & Vectors, 2022)
Abstract Background Despite decades of community-directed treatment with ivermectin (CDTI), onchocerciasis transmission persists in Cameroon and has been associated with increased risk for epilepsy in endemic communities. We investigated the onchocerciasis situation in the Ntui Health District (a known onchocerciasis focus in Cameroon where the Sanaga River constitutes the main source of black fly vectors) using parasitological, entomological and serological parameters. Methods In July 2021, community-based surveys were conducted in four villages (Essougli, Nachtigal, Ndjame and Ndowe). Onchocerciasis was diagnosed via microscopic examination of skin snips. Using rapid diagnostic tests, we screened children aged 3–6 years for Ov16 antibodies as a proxy for recent onchocerciasis transmission. Monthly black fly biting rates were obtained from the two riverside villages (Nachtigal and Essougli) for 12 consecutive months (July 2021 to June 2022) using the human landing catch technique. Some black flies were dissected each month to check for infection. Results Overall, 460 participants were recruited; mean age was 32.1 (range: 3–85) years with 248 (53.9%) being males. Among skin snipped participants (n = 425), onchocerciasis prevalence was 14.6%. Participants with epilepsy (n = 25) were more often skin snip positive (45.8% vs 12.7%; P < 0.001) and had higher microfilarial loads (9.2 ± 22.0 vs 0.7 ± 3.5 microfilariae/skin snip; P < 0.001) compared to their peers without epilepsy. Eight (6.5%) of the 123 tested children were Ov16 seropositive. The breeding sites we investigated along the Sanaga River during the current study harbored fewer vectors (annual biting rates reaching 530,322 vs 606,370 in the Mbam River) and exhibited lower black fly infection rates (annual transmission potentials reaching 1479 vs 4488 in the Mbam River) when compared to recent entomological reports in Cameroon. Conclusion Despite substantial biting rates, black fly infection rates (by microscopy) in the Ntui Health District were rather low resulting in overall low transmission potentials in study villages. Thanks to CDTI, O. volvulus infection in both humans and insects is on the decrease. However, there is evidence that O. volvulus is still endemic in these communities. Reducing the vector population will further accelerate onchocerciasis elimination prospects. Graphical Abstract